Optimization of the Level of Mushroom in Analogue Meat Nuggets - Kumar, Pavan; Sharma, B.D.; Kumar, R. R. (Journal of Meat Science, 2011)
Meat analogue is mock meat that is made from non-animal protein and its appearance and smell are very much like real meat. Analogue meat nuggets were prepared as per basic formulation under standardized processing conditions with three different levels of mushroom viz. 18%, 22.5% and 27% replacing textured soy protein. Among the physico-chemical parameters pH and protein percent decreased significantly (P<0.01) with increase in levels of incorporation whereas cooking yield increased. Moisture percent of analogue meat nuggets at 27% level of mushroom incorporation was significantly higher (P<0.01) as compared to other two levels. All the sensory attributes except general appearance and juiciness were significantly higher (P<0.01) at 22.5% mushroom level as compared to 18% and 27% levels which were comparable to each other. On the basis of sensory rating 22.5% mushroom incorporation was selected as the optimum in analogue meat nuggets.